2018
DOI: 10.1017/s0022149x18001116
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group antigens may be associated with increased susceptibility to schistosomiasis: a systematic review and meta-analysis

Abstract: Schistosomiasis or bilharzia is a widespread parasitic disease caused by blood flukes of the genus Schistosoma. Some factors have been investigated previously regarding their effect on the pathophysiological mechanism of human schistosomiasis, but the possible influence of the ABO blood group on the severity of Schistosoma infection has been the most promising. Hence, we performed a systematic review and meta-analysis to further investigate the association of the ABO blood group with schistosomiasis susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…Women of the O blood group were more susceptible to S. haematobium infection. This is not in line with previous findings [38,39] that showed the contrary. This might be due to the smaller sample size in our study and calls for further investigations in this area.…”
Section: Discussioncontrasting
confidence: 99%
“…Women of the O blood group were more susceptible to S. haematobium infection. This is not in line with previous findings [38,39] that showed the contrary. This might be due to the smaller sample size in our study and calls for further investigations in this area.…”
Section: Discussioncontrasting
confidence: 99%
“…Secondly, Koike C et al suggested that anti-A and/or anti-B antibodies may neutralize the virus to effectively protect body when polymorphic blood group antigens expressed on the surfaces of red blood cells and epithelia are utilized as attachment receptors by HIV ( Koike et al, 2007 ), perhaps for COVID-19, anti-A antibodies and/or anti-B antibodies also have the effect of neutralizing the SARS-COV-2. Thirdly, when combined anti-A or anti-B with cells of schistosome, it was suggested the unique ABO blood group antigen could confer appropriate specificity upon them ( Gardas and Kościelak, 1973 ; Dean, 1974 ; Goldring et al, 1976 ), which was regarded as one of the interpretations why O type blood is not prone to schistosomiasis ( Tiongco et al, 2018 ). Finally, it has been suggested that blood group O could prevent severe Plasmodium falciparum malaria through the mechanism of reducing rosettes ( Ja et al, 2007 ; Degarege et al, 2019 ), so we speculated that blood type O has a similar effect on SARS-COV-2.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Clinically, blood types have been linked to bacterial, parasitic, and viral infections. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 One study, in particular, found that ABO polymorphism was associated with susceptibility to infection with severe acute respiratory syndrome coronavirus (SARS-CoV)-1. 30 Further investigations discovered a protective effect of anti-A antibodies against intracellular uptake of the SARS-CoV-1 virus.…”
Section: Introductionmentioning
confidence: 99%